2015
DOI: 10.1186/s13058-015-0591-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel mammographic density loci at 6Q25.1

Abstract: IntroductionMammographic density (MD) is a strong heritable and intermediate phenotype for breast cancer, but much of its genetic variation remains unexplained. We performed a large-scale genetic association study including 8,419 women of European ancestry to identify MD loci.MethodsParticipants of three Swedish studies were genotyped on a custom Illumina iSelect genotyping array and percent and absolute mammographic density were ascertained using semiautomated and fully automated methods from film and digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
1
20
2
Order By: Relevance
“…Notably, the associations for both rs7289126 with percent density and dense area and rs7816345 with percent density could not be replicated in a recent large-scale genetic association study including about 88,400 Swedish women (26). The SNP rs4849887 in INHBB was the only SNP included in our study that was reported to be associated with nondense area at genome-wide significance level previously (10,26). We observed a similar association with nondense area in the Chinese women.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Notably, the associations for both rs7289126 with percent density and dense area and rs7816345 with percent density could not be replicated in a recent large-scale genetic association study including about 88,400 Swedish women (26). The SNP rs4849887 in INHBB was the only SNP included in our study that was reported to be associated with nondense area at genome-wide significance level previously (10,26). We observed a similar association with nondense area in the Chinese women.…”
Section: Discussioncontrasting
confidence: 67%
“…In our study however, we observed that the effects of these alleles were in the opposite direction from those reported previously, although neither of these were statistically significant. Notably, the associations for both rs7289126 with percent density and dense area and rs7816345 with percent density could not be replicated in a recent large-scale genetic association study including about 88,400 Swedish women (26). The SNP rs4849887 in INHBB was the only SNP included in our study that was reported to be associated with nondense area at genome-wide significance level previously (10,26).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Breast density is 60-70% heritable, and GWAS have identified 7 loci associated with percent dense area [37]. Our PRS includes at least two SNPs associated with density, rs10995190 (ZNF365) and rs3817198 (LSP1) and SNPs from ESR1, a locus that is associated with density [37,38]. Thus, our version of the PRS accounts for a small portion of the heritability of breast density, and inclusion of the PRS minimally affects the association between breast density and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several GWAS studies have identified SNPs at 6q25 that are associated with breast cancer risk [13,18,20,[23][24][25][26][27] and mammographic density [23,[27][28][29][30]. The initial report identified a SNP in the intergenic region between ESR1 and CDCC170 in an East Asian population [24].…”
Section: Introductionmentioning
confidence: 99%